(untitled) (Polis (Santiago), 2018)
Border migration is an increasingly important phenomenon in the region due to the current crisis context of northern countries and the economic strengthening for some South American nations as is the case of Chile. The focus of this study is female migration to the region of Tarapacá, Chile, over the past few years, the motivations for migrating, the border crossing experience, and the place of support networks in the configuration of border migration in the context of reception. The analysis of that migratory experience and the work of entities that provide pastoral care for migrants based on the testimonies of migrants themselves- allow us to explore how the community is structured at destination, its composition and monitoring in a border zone. The characteristics of migrant women and their support networks help explain their access to specific feminized employment opportunities, the fragility of their living conditions for migrant women, and border mobility strategies.